Development of erythropoietin receptor-targeted drug delivery system against breast cancer using tamoxifen-loaded nanostructured lipid carriers - Beh CY; How CW; Foo JB; Foong JN; Selvarajah GT; Rasedee A (Dove Medical Press, 2017)
Chaw Yee Beh,1 Chee Wun How,1,2 Jhi Biau Foo,2 Jia Ning Foong,3 Gayathri Thevi Selvarajah,3 Abdullah Rasedee1,3 1Laboratory of Vaccines and Immunotherapeutics, Institute of Bioscience, Universiti Putra Malaysia, Serdang, 2Faculty of Pharmacy, MAHSA University, Jenjarom, 3Faculty of Veterinary Medicine, Universiti Putra Malaysia, Serdang, Malaysia Abstract: Tamoxifen (TAM) has been used in the treatment of breast cancers and is supplemented with erythropoietin (EPO) to alleviate the cancer-related anemia. The purported deleterious effects caused by the use of EPO with chemotherapeutic agents in the treatment of cancer-related anemia vary across studies and remain controversial. The use of nanoparticles as a drug delivery system has the potential to improve the specificity of anticancer drugs. In this study, we simultaneously incorporated two pharmacological active ingredients in one nanocarrier to develop EPO-conjugated TAM-loaded lipid nanoparticles (EPO-TAMNLC), a targeted delivery system, to enhance the cytotoxic activity while reducing the side effects of the ingredients. The effect of temperature in modulating the thermodynamic parameters associated with the binding of EPO and TAMNLC was assessed using isothermal titration calorimetry, while the unfolding of EPO structure was determined using fluorescence-quenching approach. The association efficiency of EPO and TAMNLC was 55.43%. Unlike binding of albumin to TAMNLC, the binding of EPO to TAMNLC occurred through endothermic and entropy-driven reaction. The EPO-TAMNLC formulation was stable because of the hydrophobic interaction and the high free energy, suggesting the spontaneity of the interactions between EPO and TAMNLC. The EPO-TAMNLC enhanced the in vitro cytotoxicity of TAM to MCF-7 cells. The EPO surface-functionalized TAMNLC could sequentially deliver EPO and TAM as well as improving site-specific delivery of these therapeutic compounds. Keywords: tamoxifen, thermodynamic interaction, albumin